Volatile organic compounds in truffle (Tuber magnatum Pico): comparison of samples from different regions of Italy and from different seasons - Federico, Vita (Sci Rep, 2015)
In this paper volatile organic compounds (VOCs) from Tuber magnatum fruiting bodies were analyzed using a PTR-TOF-MS instrument. The aim was to characterize the VOC's profile of the fruiting bodies and identify if any VOCs were specific to a season and geographical areas. Multiple factorial analysis (MFA) was carried out on the signals obtained by MS. Experiments using ITS region sequencing proved that the T. magnatum life cycle includes the formation of fruiting bodies at two different times of the year. The VOCs profiles diverge when different seasonal and geographical productions are considered. Using PTR-TOF-MS, compounds present at levels as low pptv were detected. This made it possible to determine both the origin of fruiting bodies (Alba and San Miniato) and the two biological phases of fruiting bodies formation in San Miniato truffles.